X and Y gene dosage effects are primary contributors to human sexual dimorphism: The case of height - Alexander S. F. Berry; Brenda M. Finucane; Scott M. Myers; Christa L. Martin; David H. Ledbetter; Huntington F. Willard; Matthew T. Oetjens (Proceedings of the National Academy of Sciences, 2025)
Many human phenotypic traits vary between the sexes, including adult height for which males are, on average, 13 cm taller than females. The biological mechanisms for this sexual dimorphism are not entirely understood. One hypothesis to explain the sexual dimorphism in height relates to differential expression in males and females of SHOX , a height-related gene in the pseudoautosomal region 1 (PAR1) on the X and Y sex chromosomes. SHOX expression is reduced on the inactive X chromosome (Xi), compared to the active X in females. Sex chromosome aneuploidies (SCAs), characterized by an atypical number of X and/or Y chromosomes, serve as informative models for investigating PAR1-related gene dosage effects. Here, we leveraged three large biobanks to study 928,605 individuals, including 1,225 adults with SCAs: 45,X (n = 95), 47,XXY (n = 505), 47,XYY (n = 290), and 47,XXX (n = 335). By modeling height across individuals with various sex chromosome complements, we quantified the contributions of five sex-related genomic contributors to height, including Xi chromosome dosage, Y chromosome dosage, male sex hormones, and effects of Klinefelter and Turner syndromes. We found that a unit increase in Y chromosome dosage confers 3.1cm (95% CI, 1.9 to 4.3) more to height than a unit increase in Xi chromosome dosage, independent of hormonal variables. The larger increase in height conferred by the Y chromosome explained 22.6% of the observed difference in height between 46,XY males and 46,XX females. This finding is consistent with the hypothesis that reduced SHOX expression in females results in a net difference in height between the sexes.